Energy-Based Seismic Risk Evaluation of Tall Reinforced Concrete Building in Vancouver, BC, Canada, under Mw9 Megathrust Subduction Earthquakes and Aftershocks - Tesfamariam, Solomon; Goda, Katsuichiro (Frontiers in Built Environment, 2017)
This article presents a seismic performance evaluation framework for reinforced concrete (RC) buildings, comprising shear walls and gravity frames. The evaluation is undertaken within a performance-based earthquake engineering framework by considering regional seismicity and site-specific ground motion selection. Different engineering demand parameters (EDPs), i.e., maximum interstory drift ratio (MaxISDR) and energy-based damage index, are considered as performance indicators. Various prediction models of EDPs are developed by considering four ground motion intensity measures (IMs), i.e., spectral acceleration at the fundamental period, Arias intensity, cumulative absolute velocity (CAV), and significant duration of ground motion. For this study, a 15-story RC building, located in Vancouver, BC, Canada, is considered as a case study. By using 50 mainshock and 50 mainshock–aftershock (MS-AS) earthquake records (2 horizontal components per record and bidirectional loading), non-linear dynamic analyses are performed. Subsequently, the calculated MaxISDRs and damage indices are correlated with suitable IMs using cloud analysis, and the most efficient IM-EDP prediction models are selected by comparing standard deviations (SDs) of the regression errors. The MaxISDR of the shear walls is less than 1% for the mainshock and MS-AS records. The energy-based damage index shows sensitivity to delineate impact of earthquake types and aftershocks. The CAV is showed to be the most efficient IM for the energy-based damage index.